The importance of the medico-legal autopsy - Nadesan, K. (College of Pathologists, Academy of Medicine Malaysia, 1997)
All deaths due to unnatural causes and deaths that are believed to be due to natural causes but where the medical cause of death is not certain or known are subjected to an inquest. The objective of an inquest is to ascertain facts pertaining to the death. This is achieved by inquiry and at the conclusion of the inquest a verdict is arrived as to whether the death was due to a natural, accidental, suicidal or a homicidal cause. An inquest is not a trial. There is no complainant or defendant and at the conclusion of the inquest no judgment is passed. The inquest system exists in all parts of the world. In the English legal system, the person who conducts an inquest is called a Coroner. In Scotland, he is called a Procurator Fiscal. The United States of America use the Medical Examiner system. Most continental European countries and their former colonies follow the Code Napoleon. A postmortem examination may become necessary in certain deaths that come up for inquests. In these situations the authority which conducts the inquest will order a doctor to perform a postmortem examination (medico-legal autopsy). To perform a medico-legal autopsy, consent from the relatives of the deceased is not required. In an unexpected sudden death, only a doctor after a postmortem examination may be able to determine the cause of death. However, it is often wrongly assumed that the objective of a postmortem examination is only to ascertain the cause of death. This article deals with the purpose of the inquest and roles of the medico-legal autopsy.